Protectores ante la violencia escolar en contexto dominicano: un modelo explicativo desde la psicología positiva - Oliver Germes, Amparo (2015)
Some aggressive behaviors of adolescents in schools became a particularly important problem in Latin American and Caribbean region. Specifically, in the Dominican Republic studies report of prevalence from 21.8 to 33.6 %. The aim of this research is to study if some variables from positive psychology such as self-concept, dispositional hope, entrepreneurial attitudes, and values can act as protective factors for such violent behaviors. In order to reach our goal, a study on a sample of 117 secondary students was carried out. Assessment tool kit included, together with information on socio-demographic data, the Violent Behaviors on School Scale, the Dispositional Hope Scale, the Self-Concept 5 Scale, the Entrepreneurial Attitudes Scale for Students, and the Personal Values Questionnaire. To evaluate the relation among the different dimensions, a MIMIC (multiple indicators multiple causes) structure equation model was estimated. Under this good fitting model, hope, entrepreneurial attitudes, personal values and four dimensions of self-concept successfully predict violent behavior in school approached through a rough measurement model based on six dimensions. The model results could offer useful information from two perspectives: a) Empirically approaching to the construct school violence with satisfactory factor loadings in this latent variable; b) Identifying predictors of violence, as hope, empathy, risk-taking in context of entrepreneurship, mixed values (combination of individual and collective ones) and family self- concept. Discussion section encourages the need to work through positive psychology variables trying to decrease the presence of violent behavior in schools in the Dominican Republic.